5(3(x+2)+4)+2x=67

Simple and best practice solution for 5(3(x+2)+4)+2x=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3(x+2)+4)+2x=67 equation:


Simplifying
5(3(x + 2) + 4) + 2x = 67

Reorder the terms:
5(3(2 + x) + 4) + 2x = 67
5((2 * 3 + x * 3) + 4) + 2x = 67
5((6 + 3x) + 4) + 2x = 67

Reorder the terms:
5(6 + 4 + 3x) + 2x = 67

Combine like terms: 6 + 4 = 10
5(10 + 3x) + 2x = 67
(10 * 5 + 3x * 5) + 2x = 67
(50 + 15x) + 2x = 67

Combine like terms: 15x + 2x = 17x
50 + 17x = 67

Solving
50 + 17x = 67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-50' to each side of the equation.
50 + -50 + 17x = 67 + -50

Combine like terms: 50 + -50 = 0
0 + 17x = 67 + -50
17x = 67 + -50

Combine like terms: 67 + -50 = 17
17x = 17

Divide each side by '17'.
x = 1

Simplifying
x = 1

See similar equations:

| y=4.8+1.2 | | X=y+1.10 | | -75=-2x-3(-3x+11) | | (1.6+x)=X+8.7 | | h=-16t^2+14t+10 | | 2x+4(4x-11)=64 | | (113-x)/2=30 | | A=28x-x^2 | | 7x+5(3x-17)=113 | | 8-6x=34 | | 6x+3=5x-16 | | 5x+2(4x-17)=83 | | 4x-16=28+36 | | x+x-5.3=718.7 | | 3y+30y=3 | | 9x^2-2y^2+18=0 | | -50=4m-2 | | 3x+3(3x-5)=45 | | -20+14=m-4 | | 3x+12=2x+15 | | 38x-4=5 | | 8-6x=37 | | -3y+5=-25 | | 25+0.25(65)= | | 100=x-0.15x | | x^2+x/6-2.5+0 | | 6y-3=6y+88 | | 7x+3(3x+4)=172 | | y=3x^2+11 | | 23.3=5n-4 | | 3=1+1 | | 5x=12/1/12 |

Equations solver categories